Estradiol Synthesis and Action at the Synapse: Evidence for “Synaptocrine” Signaling - Remage-Healey, Luke; Saldanha, Colin J.; Schlinger, Barney A. (Frontiers in Endocrinology, 2011)
Classically, the modulation of brain function and behavior by steroid hormones was linked exclusively to secretion by peripheral endocrine glands. Subsequently, steroid actions within the brain were shown dependent upon either synthesis and secretion by peripheral organs or by production within the CNS itself using peripheral sources of precursors. Discovery of the estrogen-synthetic enzyme aromatase in brain further bolstered the latter view and served as a catalyst for expanding concepts of neurosteroidogenesis. In parallel research, several steroids, including estradiol, were found to have rapid effects on neuronal excitability, partially explained by novel actions at neuronal membranes. Recent findings from multiple levels of analysis and labs necessitate an updated view on how steroids are delivered to neural circuits. There is now considerable evidence for expression of the aromatase enzyme within synaptic boutons in the vertebrate CNS. Furthermore, additional work now directly couples rapid regulation of neuroestrogen synthesis with neurophysiological and behavioral outcomes. In this review we summarize evidence for targeted and acute synaptic estrogen synthesis and perisynaptic estrogen actions in the CNS of songbirds. We evaluate these findings in the context of criteria associated with classic neuromodulatory signaling. We term this novel form of signaling ‘synaptocrine’, and discuss its implications.